وسائل الضبط الاجتماعي في الأسرة السورية ( دراسة ميدانية على عينة من الأسر في مدينة اللاذقية) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
إن الهدف الأسمى للضبط الاجتماعي هو ضمان استقرار البناء الاجتماعي وزيادة تماسك المجتمع لذلك تستلزم دراسة الضبط الاجتماعي الوقوف على الوسائل التي يشكل بها المجتمع سلوك أفراده, والأجهزة التي يضعها لصيانة النظام الاجتماعي. وتختلف وسائل الضبط الاجتماعي باختلاف نوعيتها ودرجة فاعليتها من مجتمع لآخر وداخل المجتمع ذاته, فما يعتبر وسيلة ذا فاعلية في مجتمع ما قد لا يكون في مجتمع آخر بدرجة الفاعلية نفسها, والشيء ذاته في المجتمع الواحد. فالقانون مثلاً ذو درجة كبيرة من الفاعلية في المجتمعات المتقدمة عن التقاليد والأعراف والعادات, بينما تزيد فاعلية هذه الأخيرة في المجتمعات الريفية عن القانون.The ultimate goal of social control is to ensure stability of the social structure and to increase cohesion of society. So it is necessary to study social control in order to identify the means by which a community shapes the behavior of its members, and the means through which social order is maintained. Means of social control differ in quality and degree of effectiveness from one community to another and within the community itself. What is effective in a society may not be as effective in another community or society. For example, compared with traditions and customs, the law has a high level of effectiveness in developed societies, while the reverse is true in rural communities.